The Antihyperglicemic Activity of ethanol Extract of Fenugreek seed (Trigonella foenum graecum L) and its effect on the GLUT-2 expression of Streptozotocin Nicotinamide Induced Rats - Jena Hayu Widyasti; Gunawan Pamudji Widodo; Rina Herowati (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2018)
Insulin is an important factor in glucose transport. Glucose transporter (GLUT-2) in pancreatic β cell membranes is responsible for glucose transport that will stimulate insulin secretion. The purpose of this research was to investigate the antihyperglycemic activities of extract of Trigonella foenum-graecum L. (fenugreek) seed and the effects on GLUT-2 protein expression in pancreatic β cells on Streptozotocin-Nicotinamide-induced (STZ-NA) rats. This research utilized five groups of male Wistar rats. Group I was normal control group, while Groups II-V were induced with STZ-NA. Group II was negative control group (CMC Na 1%); group III was positive control group (Glibenclamide); group IV and V was examined group (fenugreek seed ethanol extract of 100mg/kg bw and 200 mg/kg bw)). The test compounds were orally administered for 14 days. Measurement of blood glucose levels and observation of the expression of GLUT-2 protein in pancreatic β cells in rats were conducted by immunohistochemistrical method. The research results revealed that the examined group dose of 200 mg/kg bw of fenugreek seed extract appeared to show blood glucose level decline that was proportionate to that of the positive control group. The increased density of GLUT-2 protein in pancreatic β cells significantly occurred in the group injected with 200 mg/kg bw compared to the group injected with 100 mg/kg bw. Hence, 200 mg/kg bw of fenugreek seed ethanol extract was able to decrease blood glucose levels and increase the GLUT-2 protein expression in pancreatic β cells in STZ-NA-induced rats with the effectiveness that was comparable to the positive control group